2018
DOI: 10.3390/nu10091208
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 Ameliorates Lipopolysaccharide-Induced Acute Lung Injury by Regulating the TLR4/PI3K/Akt/mTOR, Raf-1/MEK/ERK, and Keap1/Nrf2/HO-1 Signaling Pathways in Mice

Abstract: The anti-inflammatory effect of ginsenoside Rh2 (GRh2) has labeled it as one of the most important ginsenosides. The purpose of this study was to identify the anti-inflammatory and antioxidant effects of GRh2 using a lipopolysaccharide (LPS) challenge lung-injury animal model. GRh2 reduced LPS-induced proinflammatory mediator nitric oxide (NO), tumor necrosis factor-alpha, interleukin (IL)-1β, and anti-inflammatory cytokines (IL-4, IL-6, and IL-10) production in lung tissues. GRh2 treatment decreased the histo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Hu et al [ 28 ] demonstrate that the Nrf2-Keap1-antioxidant response element (ARE) signaling pathway can eliminate oxidative stress and its associated inflammation to improve traumatic lung injury-related pathology, and a Keap1-Nrf2 inhibitor designed by Zhang et al is expected to be a novel protective agent of ALI [ 29 ]. In addition, it has been reported that some drugs and compounds can alleviate lung injury by regulating Keap1-Nrf2 pathways, such as ginsenoside Rh2 [ 30 ], sinomenine [ 31 ], and panaxydol [ 32 ]. However, whether sevoflurane attenuates oxidative stress and subsequent inflammation responses via the Keap1-Nrf2 pathway has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [ 28 ] demonstrate that the Nrf2-Keap1-antioxidant response element (ARE) signaling pathway can eliminate oxidative stress and its associated inflammation to improve traumatic lung injury-related pathology, and a Keap1-Nrf2 inhibitor designed by Zhang et al is expected to be a novel protective agent of ALI [ 29 ]. In addition, it has been reported that some drugs and compounds can alleviate lung injury by regulating Keap1-Nrf2 pathways, such as ginsenoside Rh2 [ 30 ], sinomenine [ 31 ], and panaxydol [ 32 ]. However, whether sevoflurane attenuates oxidative stress and subsequent inflammation responses via the Keap1-Nrf2 pathway has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Hsieh et al. ( 2018 ) suggested that Rh2 ameliorated lipopolysaccharide (LPS)‐induced oxidative stress by regulating signaling pathways (HO‐1/Trx‐1/KAP‐1/Nrf2) in mice. In another study, Rh2 suppressed oxidative stress, had antioxidant activity in vivo, and restored the balance of the antioxidant defense system (Qi et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…QE was demonstrated to mediate the expression of Nrf2 and the activity of antioxidant response element (ARE)-reporter gene, thus regulating Nrf2/ARE-mediated antioxidant defense mechanism [ 43 ]. Previously, in LPS-induced lung injury in mice, the protein level of Cytosol Nrf2 was reduced after LPS treatment, while it was partially restored after GRh2 treatment, which indicated that GRh2 showed antioxidant effects by inhibiting Nrf2 nuclear translocation [ 44 ]. In the present study, we discovered that Cytosol Nrf2 was reduced, while Nucleus Nfr2 was elevated after CSE treatment, which suggested that CSE induced oxidative stress and the subsequent Nrf2 nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%